Pengaruh Fenomena Korean Wave dan Ulasan Online Terhadap Minat Halal Industry Korean Gen Z Muslim Kota Jambi - Nur ayunatasya; Ahmad syahrizal; Nurrahma sari putri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to analyze the influence of the Korean Wave phenomenon and online reviews on interest in purchasing halal Korean industry products among Gen Z Muslims in Jambi City. Data analysis uses multiple linear regression. The research results show that the Fcount value is 95.183, where this value is greater than Ftable = 2.70 (Fcount> Ftable). Furthermore, the results of the partial test show that the Korean Wave phenomenon has a significance value of 0.044 (P<0.05), so that the Korean Wave phenomenon has no effect on buying interest. Meanwhile, online reviews have a significance value of 0.000 (0<0.05). This means that reviews have a real influence on interest in buying halal industrial Korean products among gen Z Muslims in Jambi City. The coefficient of determination (R2) as seen from the Adjusted R Square value is 0.655 or 65.5%. This means that 65.5% of interest in buying halal industrial Korean products among Gen Z Muslims in Jambi City is influenced by the Korean Wave phenomenon and online reviews.